Adjuvants approved for human use: What do we know and what do we need to know for designing good adjuvants? (2023)
Adjuvants represent one of the most significant biotechnological solutions regarding vaccine development, thereby broadening the amount of candidates which can now be used and tested in vaccine formulations targeting various pathogens, as antigens which were previously discarded due to their low or null immunogenicity can now be included. Adjuvant development research has grown side-by-side with an increasing body of knowledge regarding immune systems and their recognition of foreign microorganisms. Alum-derived adjuvants were used in human vaccines for many years, even though complete understanding of their vaccination-related mechanism of action was lacking. The amount of adjuvants approved for human use has increased recently in line with attempts to interact with and stimulate the immune system. This review is aimed at summarising what is known about adjuvants, focusing on those approved for use in humans, their mechanism of action and why they are so necessary for vaccine candidate formulations; it also discusses what the future may hold in this growing research field